Alpha Band Resting-State EEG Connectivity Is Associated With Non-verbal Intelligence - Zakharov, Ilya; Tabueva, Anna; Adamovich, Timofey; Kovas, Yulia; Malykh, Sergey (Frontiers in Human Neuroscience, 2020)
The aim of the present study was to investigate whether EEG resting state connectivity correlates with intelligence. One-hundred and sixty five participants took part in the study. Six minutes of eyes closed EEG resting state was recorded for each participant. Graph theoretical connectivity metrics were calculated separately for two well-established synchronization measures (weighted Phase Lag Index and Imaginary Coherence) and for sensor- and source EEG space. Non-verbal intelligence was measured with Raven's Progressive Matrices. In line with the Neural Efficiency Hypothesis, path lengths characteristics of the brain networks (Average and Characteristic Path lengths, Diameter and Closeness Centrality) within alpha band range were significantly correlated with non-verbal intelligence for sensor space but no for source space. According to our results, variance in non-verbal intelligence measure can be mainly explained by the graph metrics built from the networks that include both weak and strong connections between the nodes.